2014
DOI: 10.1111/jfpp.12343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Chain and Long-Chain Inulin on the Quality of Probiotic Yogurt Containing L actobacillus rhamnosus

Abstract: This study investigated the effects of adding short-chain and long-chain inulins on the growth of Lactobacillus rhamnosus and the physicochemical and sensory properties (appearance, structure-texture, odor and taste) of probiotic yogurt during cold storage. The inulin-supplemented yogurt batches were compared with control batches of unsupplemented yogurt and L. rhamnosus-inoculated yogurt. The inulins were incorporated at 2% w/w in the yogurt mixtures that were inoculated with L. rhamnosus and mixed cultures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 55 publications
3
35
0
1
Order By: Relevance
“…The higher mean flavour score of the 4% SCI sample could be due to the natural sweetness of the short-chain inulin. These results are similar to the findings of Canbulat et al [20], whose study of short-chain and long-chain inulin in a probiotic yogurt revealed that short-chain inulin received higher scores for odour, taste, and overall acceptance than the yogurt with long-chain inulin. This trend is similar to the mean sweetness scores (Figure 4) and mean texture scores ( Figure 5), with 4% SCI receiving a significantly higher score (p < 0.05) than other samples.…”
Section: Sensory Evaluationsupporting
confidence: 82%
See 3 more Smart Citations
“…The higher mean flavour score of the 4% SCI sample could be due to the natural sweetness of the short-chain inulin. These results are similar to the findings of Canbulat et al [20], whose study of short-chain and long-chain inulin in a probiotic yogurt revealed that short-chain inulin received higher scores for odour, taste, and overall acceptance than the yogurt with long-chain inulin. This trend is similar to the mean sweetness scores (Figure 4) and mean texture scores ( Figure 5), with 4% SCI receiving a significantly higher score (p < 0.05) than other samples.…”
Section: Sensory Evaluationsupporting
confidence: 82%
“…Other sensory evaluation studies regarding supplementation of inulin in probiotic dairy products showed similar results [20,33]. A study done by Canbulat et al [20] reports on the higher score for odour, taste, and overall acceptability for a yogurt with short-chain inulin than for a yogurt with long-chain inulin. A study done by Aryana et al shows that flavour scores for yogurt with short-chain inulin were significantly higher than for yogurt with long-chain inulin [33].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In addition to the yogurt and dairy starter cultures, recent studies revealed the importance of the use of adjunct cultures for yogurt and other dairy products production in order to develop the technological properties of these products as well as enhance the functional properties of these products to be used as functional foods (Ekinci & Gurel, ; Sharp, McMahon, & Broadbent, ). These adjunct cultures include some other lactic acid bacteria (LAB) (Canbulat & Ozcan, ) and some Bifidobacteria species (Tejada‐Simon, Lee, Ustunol, & Pestka, ).…”
Section: Introductionmentioning
confidence: 99%